Vitamin D Levels and Their Correlation with Predisposing Factors and Estimated Fetal Weight in Third Trimester of Pregnancy: an Observational Study - Indahwati, Dwiwahju Dian; Jasaputra, Diana Krisanti; Budiono, Arief; Gunadi, Julia Windi; Lesmana, Ronny; Kusmawan, Steven Zerin Putra (Global Medical & Health Communication (GMHC), 2024)
Vitamin D has a broad impact on the human body, including affecting the bones and the immune system. Vitamin D deficiency in pregnant women is a risk factor in several circumstances, such as preeclampsia, gestational diabetes, premature birth, and low birth weight babies. This study aimed to determine the vitamin D levels and their relationship to predisposing factors and estimated fetal weight in the third trimester of pregnancy. Eighteen pregnant women in their third trimester of pregnancy who received antenatal care in the Obstetric Clinic of Immanuel Hospital Bandung from January to December 2022 were used as subjects of this study. The inclusion criteria are third-trimester pregnant women, healthy, while the exclusion criteria are currently taking drugs that have side effects in pregnancy or having pregnancy disorders. Blood was taken to measure vitamin D levels, fetal weight was estimated with obstetric ultrasound, and the subjects filled in questionnaires about predisposing factors. The results showed ten pregnant women (56%) had vitamin D deficiency below 20 ng/mL in their third-trimester pregnancy. We found non-significant relationships (p>0.05) between predisposing factors (daily consumption of vitamin D, sun exposure, maternal age), estimated fetal weight, and vitamin D levels. This study concludes that 56% of pregnant women in their third trimester of pregnancy have vitamin D deficiency with no significant relationship with its predisposing factors and estimated fetal weight.